Contributors - Lund, Jacob (The Nordic Journal of Aesthetics, 2017)
Marit Grøtta is Associate Professor of Comparative Literature at the University of Oslo, Norway. Her latest book is Baudelaire’s Media Aesthetics: The Gaze of the Flâneur and 19th-Century Media (Bloomsbury, 2015). Other publications include “Reading/Developing Images: Baudelaire, Benjamin, and the Advent of Photography,” Nineteenth-Century French Studies nr. 1-2 (2012) and “Fotografi og følelser: Om Proust, portrettfotografier og lengselen etter å nå utover seg selv,” Agora: Tidsskrift for filosofisk spekulasjon, nr. 1 (2016), as well as other articles on literature, aesthetics and media culture. Grant Kester is Professor of Art History in the Visual Arts department at the University of California, San Diego and the founding editor of FIELD: A Journal of Socially Engaged Art Criticism. His publications include Art, Activism and Oppositionality: Essays from Afterimage (Duke University Press, 1998), Conversation Pieces: Community and Communication in Modern Art (University of California Press, 2004, second edition in 2013), The One and the Many: Contemporary Collaborative Art in a Global Context (Duke University Press, 2011) and Collective Situations: Dialogues in Contemporary Latin American Art 1995-2010, an anthology of writings by art collectives working in Latin America produced in collaboration with Bill Kelley Jr. (Duke University Press, 2017). He is currently completing work on a new book that develops a more detailed theoretical account of dialogical aesthetics. Nicholas Mirzoeff is Professor of Media, Culture and Communication at New York University. Among his many publications are How To See The World (London, 2015) and the forthcoming open-source e-book The Appearance of Black Lives Matter. For more information and bibliography please visit: http://www.nicholasmirzoeff.com/bio/ Kasper Opstrup is a writer and researcher of radical culture, specialising in concatenations of art/literature, radical politics, and occultism as counter- culture and underground phenomena. Currently he is working on a postdoc project at the University of Copenhagen, supported by the Novo Nordisk Foundation, that examines aesthetic undercurrents of mystical utopianism from surrealism to the